Rapid and Widespread Distribution of Intranasal Small Extracellular Vesicles Derived from Mesenchymal Stem Cells throughout the Brain Potentially via the Perivascular Pathway - Weiwei Shen; Tongyao You; Wenqing Xu; Yanan Xie; Yingzhe Wang; Mei Cui (MDPI AG, 2023)
Intranasal administration is a promising strategy to enhance the delivery of the sEVsomes-based drug delivery system to the central nervous system (CNS). This study aimed to explore central distributive characteristics of mesenchymal stem cell-derived small extracellular vesicles (MSC-sEVs) and underlying pathways. Here, we observed that intranasal MSC-sEVs were rapidly distributed to various brain regions, especially in the subcortex distant from the olfactory bulb, and were absorbed by multiple cells residing in these regions. We captured earlier transportation of intranasal MSC-sEVs into the perivascular space and found an increase in cerebrospinal fluid influx after intranasal administration, particularly in subcortical structures of anterior brain regions where intranasal sEVs were distributed more significantly. These results suggest that the perivascular pathway may underlie the rapid and widespread central delivery kinetics of intranasal MSC-sEVs and support the potential of the intranasal route to deliver MSC-sEVs to the brain for CNS therapy.